An fMRI analysis of verbal and non-verbal working memory in people with a past history of opioid dependence - Berenbaum, Joshua G.; Nadkarni, Prianca A.; Marvel, Cherie L. (Frontiers in Neuroscience, 2023)
Working memory describes the ability to maintain and manipulate information held in mind, and it is a fundamental aspect of executive function. Within drug addiction, impairments of executive control over behavior are thought to lead to poor decision making and risky behaviors. Previous research has demonstrated working memory and executive function difficulties in opioid-dependent individuals, but the neural underpinnings of such impairments in this population are not well understood. This study used functional magnetic resonance imaging to examine the neural mechanisms involved in working memory in 13 opioid-dependent, methadone-maintained participants (OP) and 13 matched, healthy controls (HC). A Sternberg item-recognition task was administered with three conditions: (1) a ‘verbal’ condition in which participants determined whether any six visually presented target letters matched a probe item that was presented 4-6 seconds later, (2) a ‘non-verbal’ condition in which participants were presented with a Chinese character and, following a 4-6 second delay, determined whether the character matched the probe item, and (3) a ‘control’ condition in which participants were presented with three horizontal lines and following the same delay, determined whether the lines matched a probe item (always the same three lines). Functional magnetic resonance imaging (fMRI) contrasts focused on the delay (or “maintenance”) phase for verbal and non-verbal conditions relative to the control condition. Accuracy on the working memory task did not differ between groups, but the OP group was significantly slower to respond. The fMRI imaging results indicated differences in brain activity between the OP and HC groups. FMRI-guided regions of interest correlated with age of first alcohol and THC use, suggesting that early substance use, in addition to years of opioid-abuse, may have played a role in the OP group’s working memory performance. A deeper understanding of these neural differences between opioid-dependent individuals and their healthy control counterparts helps shed light on fundamental ways in which substance use impacts the brain and cognition, potentially opening up novel avenues for therapeutic targets to treat substance use disorder.